A Causal Model of The Direct and Indirect Impact of Insecure Attachment Styles on Romantic Relationship Satisfaction Mediated by Emotion Regulation Strategies and Psychological Distress - Noppaprach, Saovanee; Blauw, Jon; Tuicomepee, Arunya (Scholar: Human Sciences, 2016)
Influences of emotion regulation strategies (i.e. cognitive reappraisal, expressive suppression) and psychological distress were analyzed along direct and indirect association of insecure attachment styles (i.e., anxiety, avoidance) and romantic relationship satisfaction. N = 1,033 Thai adult participants who presently residing or working in Bangkok and being in romantic relationship were studied. Their age ranged from 18 to 60 years old (mean age 33.40, ±SD 10.72). Thai-translated versions of the instruments Experiences in Close Relationship Scale-Short Form (ECR-S), Emotion Regulation Questionnaire (ERQ), Outcome Questionnaire (OQ), and Relationship Assessment Scale (RAS) were used when collecting data and had achieved sound psychometric properties (i.e. reliability, convergent validity, and discriminant validity). Study of Path analysis upon SEM revealed that insecure attachment styles affected psychological distress and reduced romantic relationship satisfaction. Also, cognitive reappraisal was found to indirectly affect relationship satisfaction with distress cutback, and that expressive suppression could cushion insecure attachment and safeguard the relationship, despite a distress backfire.